Efecto de la adición de melatonina en el medio de maduración y/o vitrificación de ovocitos sobre la producción in vitro de embriones bovinos - Méndez, Maria S. (2020)
The effect of the addition of melatonin (Mt) on the maturation and / or vitrification of bovine oocytes on cleavage and subsequent embryonic development was evaluated. Oocyte-cumulus cell complexes (COCs) were obtained from creole cows by ovum pick up (OPU) and by follicular aspiration from abattoir ovaries (AO). From the pool of oocytes obtained from both sources, those with homogenous cytoplasm and three or more compact layers of cluster cells were selected. The selected COCs were randomly assigned to five treatments: T1, matured with Mt and vitrified without Mt; T2, matured and vitrified with Mt; T3, matured without Mt and vitrified with Mt; T4 (control) matured and vitrified without Mt; T5, matured without Mt and not vitrified. The concentration of Mt in the maturation and vitrification media was 0.01 μM (10-9 M). The oocytes were matured, vitrified, fertilized and the presumed zygotes cultured until day 7 post-fertilization in vitro. The data were analysed by logistic regression. Regardless of the origin of the oocytes, cleavage rate (C) and embryo production (EP) was similar between treatments. The C in the OPU oocytes was greater in T4, and the EP was similar between treatments. In AO, the results did not vary between treatment in C and EP. In conclusion, Mt reduced the C in oocytes collected by OPU, while it did not affect EP. In the AO oocyte source, the addition of Mt did not affect the C nor the EP.